Revenue collection contracts in the municipality of Coimbra (Portugal): the role of transaction costs and risk in contract choice (1557-1836) - dos Santos Barbosa, José Luís (Investigaciones de Historia Económica, 2025)
This study aims to analyse revenue collection contracts in the municipality of Coimbra (Portugal), from 1557 to 1836. It will focus on examining the role of transaction costs and risk in contract selection. It is documented that from the sixteenth century to the early nineteenth century, the municipality of Coimbra used three types of contracts with private contractors, namely fixed-price, salary, and sharing contracts, although most were of the fixed-price type. The central question explored here is the influence of transaction costs and risk on the decision-making process for indirect collection contracts. The findings indicate that the municipality aimed to minimize both transaction costs and risk, leading mainly to the use of fixed-price contracts. In this arrangement, the agents (revenue contractors) bore responsibility for both the risk and the costs associated with the collection process. From 1739 onwards, the municipality shifted to direct rather than indirect collection methods, introducing additional constraints.